ナンキョク ロケット カンソク ケイカク - 木村, 磐根; キムラ, イワネ; KIMURA, Iwane (国立極地研究所, 1979)
P(論文) 南極昭和基地におけるロケット実験の将来計画を立てるにあたり,すでに一部実施され,また,一部実験実施が残っている昭和基地のIMSロケットプロジェクトについて十分検討し,反省すべきところは反省しなければならない.ポストIMSプロジェクトとしては,まずロケットテレメータの送信機をパワーアップして,データ伝送の広帯域化をはかる必要がある.観測内容については,現IMSプロジェクトのほとんどすべてが,再び実験されるであろうが,さらに装置の信頼度を上げる必要がある.また,S-500型ロケットの開発により,大形の複雑な搭載機器でのロケット実験が可能になる. Before planning future rocket exoeriments at Syowa Station in Antarctica, the IMS rocket projects already partly made and partly to be made at Syowa Station have been critically examined. For the post-IMS project, it is first proposed that the bandwidth of data transmission by rocket telemetry must be widened by powering up of the rocket-borne transmitter and by reconstructing the ground-based telemetry receiver. As to the kinds of observation, almost all IMS projects will be tried again with improving reliability of the experiments. A big comnlex payload will become feasible by an appearance of the S-500 type of rocket. departmental bulletin paper